Software preference for online learning of science and biology teachers under COVID-19 pandemic - Firas Khaleyla; Wisanti Wisanti; Reni Ambarwati; Dwi Anggorowati Rahayu; Eva Kristinawati Putri (University of Muhammadiyah Malang, 2021)
As measure against the rapid spreading of coronavirus disease 2019 (COVID-19) which now has reached global level, Indonesian government established Large-scale Social Distancing (LsSD). As consequence, learning method used in junior and senior high school is substituted from face-to-face learning in class to online distance learning, including for science and biology. This study was conducted to know software preference used by science and biology junior and senior high school teachers for online learning during LsSD measure. A total of 189 science and biology junior and senior high school teachers from various area had given their response via questionnaire. Data was analyzed using quantitative descriptive method. About 57% respondents had never manage online learning before COVID-19 pandemic while the remaining 43% had experience in managing one before, however almost all managed online learning. Non-paid software used the most (81%) among respondents to manage online science/biology learning. Software types used were social networking (64%) especially WhatsApp, learning management system (LMS) (51%) especially Google Classroom, teleconference applications (12%), and assessment software outside of LMSs (15%). Software chosen were mostly non-paid, easily accessed by all people, already familiar among Indonesian, and its interface were easily mastered.